2021
DOI: 10.1155/2021/3741413
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Malaria and Associated Knowledge, Attitude, and Practice among Suspected Patients in Bahir Dar Zuria District, Northwest Ethiopia

Abstract: Background. Control and prevention activities have brought substantial decline of malaria incidence in the last two decades in Ethiopia. However, lack of local data on the disease transmission and community knowledge, attitude, and practice about malaria are thought to reverse the trend of malaria in certain areas. Therefore, assessment of the prevalence and community awareness towards malaria plays pivotal role for the success of malaria control and prevention. Objective. To assess malaria prevalence and know… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

4
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 22 publications
4
0
2
Order By: Relevance
“…Conversely, considerably higher proportion of males (54.5%) had poor practices towards malaria than females (43.0%). This is in conformity with the finding that reported statistically significant association between practice level and gender of participants, in which greater proportion (45.0%) of female participants had good practice towards malaria than males (28.1%); contrarily, substantially higher percentage (71.9%) of male participants had poor practice level towards malaria as compared with female participants (55.0%) [ 45 ]. This could be due to the fact that women in developing countries mainly take the role of looking after their family members.…”
Section: Discussionsupporting
confidence: 90%
“…Conversely, considerably higher proportion of males (54.5%) had poor practices towards malaria than females (43.0%). This is in conformity with the finding that reported statistically significant association between practice level and gender of participants, in which greater proportion (45.0%) of female participants had good practice towards malaria than males (28.1%); contrarily, substantially higher percentage (71.9%) of male participants had poor practice level towards malaria as compared with female participants (55.0%) [ 45 ]. This could be due to the fact that women in developing countries mainly take the role of looking after their family members.…”
Section: Discussionsupporting
confidence: 90%
“…Previously, the Ethiopian Public Health Institute designated areas above 2000 m altitude as malaria-free zones, although not totally malaria-free at the district level [ 35 ]. However, this study result and other studies reported high malaria burden in areas with such altitude [ 15 , 16 , 26 , 36 ].…”
Section: Discussioncontrasting
confidence: 83%
“…About 86.0% students, in this study, admitted that fever was the most recognized symptoms of malaria. This is in contrast toDejazmach et al (2021) who reported chills and shivering as most recognized symptoms but is similar to a study by Olusegun-Joseph et al (…”
supporting
confidence: 89%